(untitled) (Bioscience Journal, 2023)
Wound healing remains a clinical problem, with cases of atrophic, hypertrophic, or keloid scars. Three-dimensional scaffolds have been used to restore skin function, facilitating cell migration, adhesion, and proliferation. Collagen is the most common, presenting low antigenicity, decreased inflammation, and replacement by autologous tissue. It is used as sheets/films, sponges, membranes, sprays, and hydrogels of various origins. This integrative literature review aimed to evaluate the application of unassociated collagen scaffolds for skin wound healing and compare them to collagen associations with nanomaterials and polymers. Properties such as applications in humans and other unconventional models cause burns, partial and full-thickness wounds, and others. Scaffold, biomaterials, collagen, wound, injury, repair, and healing were among the descriptors. We found 3,098 articles published between 1995 and 2022 (Mendeley platform), including clinical/experimental trials. After exclusion, 26 studies were identified and analyzed. Autologous and heterologous collagens are the most used in the clinic and favor wound closure by improving re-epithelialization and reducing inflammation but may present challenges in aesthetic acceptance and loss of repair function in the wound site. Furthermore, collagen integration with other nanomaterials improved wound repair and experimental models.